Genome-wide linkage mapping of Fusarium crown rot in common wheat (Triticum aestivum L.) - Li, Faji; Guo, Can; Zhao, Qi; Wen, Weie; Zhai, Shengnan; Cao, Xinyou; Liu, Cheng; Cheng, Dungong; Guo, Jun; Zi, Yan; Liu, Aifeng; Song, Jianmin; et al. (Frontiers in Plant Science, 2024)
Abstract: Fusarium crown rot (FCR) is a severe soil-borne disease that globally affects wheat and leads to significant yield reductions. Identifying loci associated with resistance to FCR and developing corresponding markers are essential for the breeding of resistant wheat varieties. In this study, we evaluated the resistance to FCR in a recombinant inbred line (RIL) population originated from Gaocheng 8901 and Zhoumai 16 across four environments. The RILs and their parents were genotyped by wheat 90K single-nucleotide polymorphism (SNP) array. We have identified a total of five quantitative trait loci (QTLs) related to FCR resistance: QFCR.caas-3AL, QFCR.caas-3DL, QFCR.caas-5BL, QFCR.caas-6BS, and QFCR.caas-7DS. These QTLs accounted for 4.6% to 12.8% of the phenotypic variance, respectively. Notably, QFCR.caas-5BL and QFCR.caas-6BS had been previously detected, whereas QFCR.caas-3AL, QFCR.caas-3DL and QFCR.caas-7DS are novel loci. The favorable alleles of QFCR.caas-3DL and QFCR.caas-5BL were contributed by Zhoumai 16, while the favorable alleles for QFCR.caas-3AL, QFCR.caas-6BS, and QFCR.caas-7DS were originated from Gaocheng 8901. Additionally, this study identified seven candidate genes that encode disease resistance proteins, the BTB/POZ domains, peroxidase activity, and leucine-rich repeat receptor-like protein kinase. Furthermore, we developed and validated two kompetitive allele-specific PCR (KASP) markers, Kasp_3AL_FCR (QFCR.caas-3AL) and Kasp_5BL_FCR (QFCR.caas-5BL), in a natural population of 202 wheat varieties. This study contributes new genetic insights and provides new stable loci and breeding available KASP markers to enhance FCR resistance in common wheat.